PENGARUH INOVASI PRODUK, KEMASAN, DAN VARIASI PRODUK TERHADAP MINAT BELI ICE CREAM AICE DI KOTA PADANG - Tika Afriyanti; Rose Rahmidani (Universitas Negeri Padang, 2019)
This study aims to know and prove how much influence Innovation Product,Packaging, and Product Varians to Purchase Intention at ice cream Aice in Padang City.This type of research is causative. The population in this study were peoples in Padang City with characteristic know about inforormation Aice and never buying ice cream Aice. The samples were taken using Cochran formula with 100 respondents. This sampling technique is based on nonprobability sampling method. The type of data used in this study is primary data. Data analysis technique used multiple regression analysis technique using SPSS version 25.00. The results of this study indicate that: 1) Innovation Product has a negatif significant effect on purchase intention, 2) Packaging has a positif signifikan effect on purchase intention, 3) Product Varian has a positive significant effect on purchase intention.Keywords: Product Innovation,Packaging, Product Varians, Purchase Intention